Ask Question
16 April, 03:09

What is the factored form of y = x2 - 4x + 3? y = (x - 4) (x - 1) y = (x - 3) (x - 1) y = (x - 2) (x - 2) y = (x + 1) (x + 3)

+3
Answers (2)
  1. 16 April, 04:47
    0
    y = (x - 3) (x - 1)

    Step-by-step explanation:

    To factor consider the factors of the constant term ( + 3) which sum to give the coefficient of the x - term ( - 4)

    The factors are - 3 and - 1, hence

    y = x² - 4x + 3 = (x - 3) (x - 1)
  2. 16 April, 04:53
    0
    Y = (x - 3) (x - 1)

    Step-by-step explanation:

    Y = x ^ 2 - 4 x + 3

    x ^ 2 - 3 x - x + 3

    x (x - 3) - 1 (x - 3)

    (x - 3) (x - 1)

    y = (x - 3) (x - 1)
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “What is the factored form of y = x2 - 4x + 3? y = (x - 4) (x - 1) y = (x - 3) (x - 1) y = (x - 2) (x - 2) y = (x + 1) (x + 3) ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers